A theoretical quantitative estimation of acidity of uracil and its derivatives through the pKa values. Issue 12 (3rd August 2018) - Ilyina, Margarita G.; Khamitov, Edward M.; Mustafin, Akhat G.; Khursan, Sergey L.
Abstract : In this paper, we propose a computational scheme for the theoretical estimation of gas‐phase acidity of uracil and its derivatives. The calculation of the acidities (р K а ) of the compounds under study was performed using quantum chemical calculations with the composite G3MP2B3 method. The solvent effect was taken into account within the polarizable continuum model and density functional theory calculations by the Polarizable continuum model (solvate model density) ‐ the exchange functional of Tao, Perdew, Staroverov, and Scuseria method. We evaluated the influence of the nonspecific solvation using two approaches (single‐point calculations versus full optimization of the studied structures) and found that the use of full optimization of the geometry of the compound for calculating the solvent effect significantly enhances the accuracy of numerical estimation of the р K а values. The mean absolute deviation decreases by 0.60 and 0.37 units of р K а in the case of the single‐point and full‐optimization approaches, respectively. The most pronounced advantage of the latter approach is its universality. Indeed, because of the implicit accounting of solvation, this computational scheme may be applied to the calculations of the р K а values of any class of compounds without reservations. The proposed computational scheme for the estimation of acidity opens new opportunities for further studies in the field of acidity. Abstract : We propose a computational scheme for the theoretical estimation of gas‐phase acidity of uracil and its derivatives. The calculation of the acidities (р K а ) of the compounds under study was performed using quantum chemical calculations with the composite G3MP2B3 method.